THE EFFECT OF CAPITAL STRUCTURE, LIQUIDITY, AND PROFITABILITY ON FIRM VALUE: EVIDENCE FROM CONSUMER NON-CYCLICALS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Lilis Sulastri; Iman Supratman; Devani Ainun Pradiva; Ruhenda; Neli Yuliyani (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the effect of capital structure (Debt-to-Equity Ratio), liquidity (Current Ratio), and profitability (Return on Assets) on firm value (Price-to-Book Value) in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX). Using the latest publicly available financial statements, we conducted an Ordinary Least Squares (OLS) regression. Results show that profitability has a significant positive effect on firm value, capital structure has a positive but marginal effect, and liquidity has a negative but insignificant effect. The findings support the Trade-Off Theory, Agency Theory, and Resource-Based View, highlighting profitability as the most influential factor in determining firm value. Using a cross-sectional sample of seven leading companies in the sector, we employ Price-to-Book Value (PBV) as the proxy for firm value, Debt-to-Equity Ratio (DER) for capital structure, Current Ratio (CR) for liquidity, and Return on Assets (ROA) for profitability. The results, based on Ordinary Least Squares regression, indicate that profitability has the strongest positive relationship with firm value, capital structure exhibits a positive relationship, and liquidity shows a negative association. However, due to the small sample size, the relationships are not statistically significant. The findings offer preliminary evidence and implications for managerial policy and investment analysis in Indonesia’s consumer goods sector.